Generative AI in Higher Education: Perception and Attitude of Students from a University in South Africa - Megbowon, Funmilola Kemi (Studies in Learning and Teaching, 2025)
This study explores the perception and attitude of university students in a South Africa-based institution towards generative AI. The specific objectives of the study are to i) examine students’ attitude towards generative AI, ii) assess students’ perceptions of the impacts of generative AI on learning dynamics, and iii) access students’ views regarding the ethical use of generative AI. Premised on the Technology Acceptance Model, the study takes an exploratory approach hence, a qualitative research method that allows gathering of non-numeric data was adopted. Data was obtained through open-ended structured interviews from first-, second-, and third-year students of the Department of Arts. Generally, the findings indicate a positive attitude towards the use of generative AI with the recognition of generative AI-embedded tools’ potential in enhancing learning by providing personalized learning support and tailored learning resources. In terms of attitude, a mix of excitement, skepticism, ethical concerns evaluative trust in generated information, and reflective compliance was observed. Equally, while generative AI was agreed to be an ethical learning aid, it was, however, perceived that ethics in its use are to be dependent on context, intent, and personal accountability. The study concludes on the need for institutions to create awareness, guidelines, and training to address issues on the ethical use of GenAI tools by higher education students.